CT angiography with 15 mL contrast material injection on time-resolved imaging for endovascular abdominal aortic aneurysm repair. Issue 126 (May 2020) - Horinouchi, Hiroki; Sofue, Keitaro; Nishii, Tatsuya; Maruyama, Koji; Sasaki, Koji; Gentsu, Tomoyuki; Ueshima, Eisuke; Okada, Takuya; Yamaguchi, Masato; Sugimoto, Koji; Murakami, Takamichi
Highlights: A third-generation dual-source CT scanner acquired time-resolved whole-aorta CTA. Temporal MIP from time-resolved imaging with 15 mL CM provided whole-aorta CTA. CTA using temporal MIP on time-resolved imaging with 15 mL CM is feasible for EVAR. Abstract: Purpose: To assess the utility of whole-aorta CT angiography (CTA) with 15 mL contrast material (CM) on time-resolved imaging for endovascular abdominal aortic repair (EVAR). Methods: Twenty-six patients with a high-risk of post-contrast acute kidney injury (PC-AKI) underwent CTA with 15 mL CM using temporal maximum intensity projection (tMIP-CTA) generated from time-resolved imaging. The aortoiliac CT values were measured. Two observers measured the arterial diameters in unenhanced CT and tMIP-CTA images, and image quality was evaluated on a 5-point scale. The presence of the accessory renal artery, inferior mesenteric artery (IMA) occlusion, and instructions for use (IFU) of EVAR were evaluated. Results: CT examinations were successfully performed, and no patients developed PC-AKI. The mean CT values of the whole aorta were 267.5 ± 51.4 HU, which gradually decreased according to the distal levels of the aorta. Bland-Altman analysis revealed excellent agreement for the external arterial diameter measurements between unenhanced CT and tMIP-CTA. Excellent interobserver agreement was achieved for the measurements of the external (ICCs, 0.910–0.992) and internal arterial diameters (ICCs, 0.895–0.993). Excellent or good overall image quality was achieved in 24 (92 %) patients. The presence of the accessory renal artery, IMA occlusion and the assessment of IFU were in 100 % agreement. Multivariate analysis revealed aortic volume as the most significant independent factor associated with strong aortic enhancement (p = 0.004). Conclusions: Whole-aorta tMIP-CTA on time-resolved imaging is useful for maintaining contrast enhancement and image quality for EVAR planning, and can substantially reduce the amount of CM.